Homeodomain-interacting protein kinase promotes tumorigenesis and metastatic cell behavior - Jessica A. Blaquiere; Kenneth Kin Lam Wong; Stephen D. Kinsey; Jin Wu; Esther M. Verheyen (The Company of Biologists, 2018)
Aberrations in signaling pathways that regulate tissue growth often lead to tumorigenesis. Homeodomain-interacting protein kinase (Hipk) family members are reported to have distinct and contradictory effects on cell proliferation and tissue growth. From these studies, it is clear that much remains to be learned about the roles of Hipk family protein kinases in proliferation and cell behavior. Previous work has shown that Drosophila Hipk is a potent growth regulator, thus we predicted that it could have a role in tumorigenesis. In our study of Hipk-induced phenotypes, we observed the formation of tumor-like structures in multiple cell types in larvae and adults. Furthermore, elevated Hipk in epithelial cells induces cell spreading, invasion and epithelial-to-mesenchymal transition (EMT) in the imaginal disc. Further evidence comes from cell culture studies, in which we expressed Drosophila Hipk in human breast cancer cells and showed that it enhances proliferation and migration. Past studies have shown that Hipk can promote the action of conserved pathways implicated in cancer and EMT, such as Wnt/Wingless, Hippo, Notch and JNK. We show that Hipk phenotypes are not likely to arise from activation of a single target, but rather through a cumulative effect on numerous target pathways. Most Drosophila tumor models involve mutations in multiple genes, such as the well-known RasV12 model, in which EMT and invasiveness occur after the additional loss of the tumor suppressor gene scribble. Our study reveals that elevated levels of Hipk on their own can promote both hyperproliferation and invasive cell behavior, suggesting that Hipk family members could be potent oncogenes and drivers of EMT.